THEORY OF MODELING: THEORY OF MODELING - Dimanova , Donika (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The aim of this study is to provide a brief introduction to the theory of modeling, to classify the models and methods of modeling, to explore the most common tools for modeling and simulation. This is necessary to specify the main characteristics on which to compare the qualities of the means of modeling and simulation and to compare these tools based on specified characteristics. Results of the study can be applied to using simulation tools (the choice of situational model ) for crisis management.